2000
DOI: 10.1152/jappl.2000.89.6.2325
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in muscle inflammation after eccentric exercise

Abstract: Unaccustomed exercise is followed by delayed-onset muscle soreness and morphological changes in skeletal muscle. Animal studies have demonstrated that women have an attenuated response to muscle damage. We studied the effect of eccentric exercise in untrained male (n = 8) and female (n = 8) subjects using a unilateral exercise design [exercise (Ex) and control (Con) legs]. Plasma granulocyte counts [before (Pre) and 48 h after exercise (+48h)] and creatine kinase activity [Pre, 24 h after exercise (+24h), +48h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
176
3
17

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(211 citation statements)
references
References 38 publications
10
176
3
17
Order By: Relevance
“…It has been found that there are significantly fewer inflammatory cells (neutrophils and granulocytes) infiltrating the vastus lateralis muscle of female university students after a standardised pain-inducing eccentric exercise compared to males. (32) Infiltration of the muscle with leucocytes and macrophages is important for satellite cell activation and initiation of muscle regeneration. Therefore, the oestrogen-attenuating effects on leucocyte infiltration may delay important stages in muscle recovery.…”
Section: International Association Of Athletics Federations Worldmentioning
confidence: 99%
“…It has been found that there are significantly fewer inflammatory cells (neutrophils and granulocytes) infiltrating the vastus lateralis muscle of female university students after a standardised pain-inducing eccentric exercise compared to males. (32) Infiltration of the muscle with leucocytes and macrophages is important for satellite cell activation and initiation of muscle regeneration. Therefore, the oestrogen-attenuating effects on leucocyte infiltration may delay important stages in muscle recovery.…”
Section: International Association Of Athletics Federations Worldmentioning
confidence: 99%
“…Post-injury pain induced by exercise frequently has its peak between 24 to 48 post-exercise hours. Muscular injury induced by performance of an eccentric exercises bout may be derived from connective tissues rupture ligated to adjacent myofibrils from the muscular cell itself, from the basal laminate adjacent to the plasmatic membrane, the plasmatic membrane of the muscular cell, the sarcomere, the plasmatic reticule, or even of a combination of these components (1)(2)(3)(4) . Muscular fibers injuries are usually evaluated by the determination of the reflux of cytosolic enzymes specific for blood circulation, combined with histological techniques or ultrastructural evaluation through electronic microscopy in order to evaluate the local effects.…”
Section: Muscular Injury Induced By Exercisementioning
confidence: 99%
“…The injury usually becomes more extensive during the next 48-72 post-exercise hours. The histological observation of the injured muscle may be characterized by the myofibrillar rupture, irregular structures of the Z lines, sarcolemma rupture, irregular location of organelles, increase of the mitochondrial density and the myofibrillar proteins and cytoskeleton content (3)(4) . The increase of cytosolic proteins in the circulation after exercise reflects the muscular injury.…”
Section: Muscular Injury Induced By Exercisementioning
confidence: 99%
See 2 more Smart Citations